America's first black socialist : the radical life of Peter H. Clark - Taylor, Nikki Marie, 1972- (The University Press of Kentucky, 2013)
In pursuit of his foremost goal, full and equal citizenship for African Americans, Peter Humphries Clark (1829--1925) defied easy classification. He was, at various times, the country's first black socialist, a loyal supporter of the Republican Party, and an advocate for the Democrats. A pioneer educational activist, Clark led the fight for African Americans' access to Ohio's public schools and became the first black principal in the state. He supported all-black schools and staunchly defended them even after the tide turned toward desegregation. As a politician, intellectual, educator, and.